Penerapan Media Pembelajaran Berbasis Wordwall Untuk Meningkatkan Motivasi dan Hasil Belajar IPAS pada Murid Kelas V.A UPT SPF SDN Gunung Sari I Makassar - Burhan, Nurhidayah; Yunus, Muh; Iskandar, Arifuddin (CV. Rayyan Dwi Bharata, 2025)
This study aims to determine the application of Wordwall-based learning media in increasing the motivation to learn science in grade V.A UPT SPF SDN Gunung Sari I Makassar and to find out the application of Wordwall-based learning media in improving social science learning outcomes in grade V.A UPT SPF SDN Gunung Sari I Makassar. The method used is classroom action research which aims to increase the motivation and learning outcomes of social studies through the application of Wordwall-based learning media to students in class V.A UPT SPF SDN Gunung Sari I Makassar. The subject of this study is a student of class V.A UPT SPF SDN Gunung Sari I Makassar with a total of 23 students, consisting of 13 boys and 10 girls. This research was carried out in two cycles, namely cycle I which was carried out 3 meetings (the first and second meetings for the learning process and the third meeting for the assessment of science and science learning outcomes) and cycle II was also carried out 3 meetings. The two cycles were carried out for 2 months plus summarizing all existing research results. The results of the study show that the application of Wordwall-based learning media has succeeded in significantly increasing students' motivation and learning outcomes of social sciences. In cycle I, the average percentage of student learning motivation indicators was 97%. In the second cycle, there was a significant increase of 29% to 88%. This means that the average percentage of student motivation indicators has exceeded the set success criteria of 75%. The application of Wordwall-based learning media can improve student learning outcomes. This is evidenced by the percentage of students who achieved KKTP scores in the first cycle of 35% increased to 87% in the second cycle. This means that the number of students who have achieved the KKTP score (70) has exceeded the set success criterion of 75%.